A preliminary examination of the relationship between biomechanical measures and structural changes in the brain. (January 2021) - Post, Andrew; Hashim, Eyesha; Hoshizaki, T Blaine; Gilchrist, Michael D; Cusimano, Michael D
Introduction: Currently, biomechanics has not been able to effectively predict when a mild traumatic brain injury may occur as a result of head impact. To improve prediction of brain trauma and the development of protective innovations, it is important to create an understanding of the relationship between the biomechanics of the head impact event and the structural damage incurred by the brain as a result of that event. The purpose of this research was to examine the relationship between diffusion tensor imaging measures and biomechanical characteristics of a head impact. Methods: Diffusion tensor imaging was conducted on concussed subjects to identify regions of white matter structural differences. The injury event was reconstructed using physical and finite element methods to identify the biomechanical parameters of the impact as well as strain to the regions of the brain. Results: A significant relationship was found between shear strain, rotational acceleration, and impact velocity on increases in radial diffusivity and mean diffusivity in the fornix. Linear acceleration was also found to have a weaker but significant relationship with a decrease in radial diffusivity in the cingulum hippocampus. Conclusion: These results demonstrate that impacts resulting in high shear strains may affect radial diffusivity and mean diffusivity measures, and that impact mechanics likely have an important role in what regions may present differences in diffusion tensor imaging measures.